(untitled) (Journal of Hama University, 2020)
Knowledge and attention to the issue of reproductive health is of great importance to university youth as they are growing and are about to enter or have already entered into family life. Sex and reproduction are fundamental aspects of it. The objective of this descriptive study was to evaluate the data of 200 Tishreen University students on reproductive health in April 2019. They were selected using a simple random sample method, which collected data using a pre-prepared questionnaire. Nearly half of the students believed that reproductive health meant reproductive integrity, and that young people were the most appropriate stage to obtain information about the reproductive system, and that the mother was their preferred source of information. 88% know that cervical cancer is a disease that may be a barrier to reproduction; 64% know that the risk of out-of-wedlock is social ostracism in the event of a scandal, and 66% say AIDS is transmitted through sex. 74% reported that smoking affects reproduction and reproductive health. The study recommended that curricula and university programs in various disciplines should include student education programs on reproductive health, the need to repeat this study in all university specialties and a larger sample to see if it would achieve the same results. and study of the effectiveness of an education and training program based on improving university students’ information on reproductive health.